Unopposed Estrogen and Endometrial Carcinogenesis: Current Concepts - Siti Salima (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Endometrial carcinoma represents the sixth most frequently diagnosed malignancy affecting the female genital tract globally.1 In 2020, approximately 417,000 new cases were identified worldwide, accompanied by an estimated 97,000 related deaths.2 Across Europe, the burden of disease remains substantial, with projections indicating 124,874 newly diagnosed cases and 30,272 deaths in 2022.3-5 The incidence of endometrial cancer continues to increase, largely driven by demographic aging and the rising prevalence of obesity. Over a woman’s lifetime, the risk of developing endometrial cancer is estimated at around 3%, with a median age at diagnosis of 61 years.6 Notably, the global incidence has risen by approximately 132% during the past three decades, underscoring the expanding impact of key risk factors, particularly obesity and population aging.